Development of a Smart Mobile Application for Student Time Management - Abdurrohman Abdurrohman; Wemby Juniarrochman (Journal of Technology and Engineering, 2026)
This study explores the development of a smart mobile application for student time management through a library research approach. The purpose of the study is to identify the conceptual foundations, functional requirements, and development opportunities for a mobile application that can support students in managing their academic time more effectively. The reviewed literature shows that students frequently struggle with task organization, prioritization, and maintaining consistent study routines. The findings indicate that a smart mobile application should integrate scheduling, reminders, progress tracking, personalized suggestions, and user-friendly interfaces to enhance academic productivity. The literature also emphasizes the importance of behavioral support and contextual relevance in improving application effectiveness. Based on the synthesis of sources, the study concludes that a smart mobile application has strong potential to serve as an adaptive digital assistant for students. Although this study is limited to conceptual analysis, it provides a practical foundation for future prototype design and empirical testing.